2003
DOI: 10.1046/j.1365-2036.2003.01757.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of antibiotic sensitivity testing before first‐line Helicobacter pylori eradication treatments

Abstract: SUMMARYBackground: The resistance of Helicobacter pylori to antibiotics has been advocated as a major cause of treatment failure, and antimicrobial sensitivity testing has been proposed to improve efficacy; however, its role before firstline therapy has not been investigated in detail. Aim: To assess whether antimicrobial sensitivity testing improves the eradication rate of first-line anti-Helicobacter treatments and to compare the effectiveness of ranitidine bismuth citrate and omeprazole in the presence of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 61 publications
0
45
0
Order By: Relevance
“…Figure 1 details the procedure of study selection in the flow chart. Thirteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25] were qualified in this meta-analysis. Tables 1 and 2 set 2 different control groups, respectively, which were labeled as group a and b in our study (e.g., Lee a and Lee b).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 details the procedure of study selection in the flow chart. Thirteen studies [13][14][15][16][17][18][19][20][21][22][23][24][25] were qualified in this meta-analysis. Tables 1 and 2 set 2 different control groups, respectively, which were labeled as group a and b in our study (e.g., Lee a and Lee b).…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Ten tailored regimens [14][15][16][17]19,[21][22][23][24][25] were designed according to pretreatment susceptibility testing (pooled RR ¼ 1.17, 95% CI 1.11-1.24). Three other studies 13,18,20 advanced their susceptibility-guided therapy by additionally adjusting their PPI administration (either by dosage adjustments or by changing drugs) on the basis of CYP2C19 polymorphism (pooled RR ¼ 1.14, 95% CI 1.01-1.28).…”
Section: Types Of Tailored Regimensmentioning
confidence: 99%
“…Pretreatment susceptibility testing was shown to be cost saving and associated with higher eradication rates (21); other data question the use of prior susceptibility testing before the use of first-and second-line therapies (16,18). These conflicting results are probably due to the different study settings and the different patients evaluated.…”
Section: Fig 2 Proportions Ofmentioning
confidence: 99%
“…Of the six potential eligible articles, we excluded another one which focused on second-line treatment for H. pylori infection (39). Five RCTs (n=701 patients) were included at last (28)(29)(30)(31)(32). The quality of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidences [included randomized controlled trials (RCTs)] suggest antibiotic sensitivity testing results in improving eradication rate (26)(27)(28)(29)(30)(31). Nevertheless, the effects still remain controversial (32)(33)(34). Furthermore, whether or not culture-guided therapy is cost saving is another bone of contention, compared to standard treatment (30,31,35,36 (38) …”
Section: Introductionmentioning
confidence: 99%